Hubungan Pola Menstruasi dengan Kejadian Anemia pada Remaja Putri di SMPN 18 Banjarmasin - M. Hafiz Ansari; Farida Heriyani; Meitria Syahadatina Noor (Homeostasis, 2020)
Abstract: Anemia is a condition when the level of hemoglobin in the blood is below normal. Data from Banjarmasin City Health Department 2018 showed there were 924 cases of anemia adolescents (age 10-19 years old), consists of 884 young females and 40 young males. Menstruation is a factor incidence anemia. This study aims to determine any association between the cycle, duration and volume of menstrual blood with the incidence of anemia in adolescent females at SMPN 18 Banjarmasin. Observational method and cross-sectional approach. The population in this study female students in SMPN 18 Banjarmasin, and 50 samples are obtained. A proportional random sampling technique is used in this study. Data analysis in this study using chi-square test with fisher’s exact test as the alternative. The results of this study showing there were 42% respondents with anemia and 58% without anemia, 40% with menstrual cycle at risk and 60% without risk, 42% with menstrual duration at risk, and 58% without risk, and 16% with menstrual blood volume at risk and 84% without risk. The results of the chi-square analysis showed that there was an association between the cycle and menstrual duration with the incidence of anemia in adolescent females at SMPN 18 Banjarmasin p=0,000, p=0,000. The result of fisher’s exact test analysis showed no association menstrual blood volume and the incidence of anemia in adolescent females at SMPN 18 Banjarmasin p=0,056. Keywords: menstrual cycle, menstrual length, menstrual blood volume, anemia, adolescents females Abstrak: Anemia adalah kondisi saat kadar hemoglobin dalam darah dibawah nilai normal. Data Dinas Kesehatan Kota Banjarmasin 2018 angka kejadian anemia remaja (usia 10-19 tahun) di Kota Banjarmasin terdapat 924 kasus, 884 remaja putri dan 40 remaja putra. Menstruasi merupakan faktor risiko terjadinya anemia. Penelitian ini bertujuan mengetahui hubungan siklus, lama dan volume darah menstruasi dengan kejadian anemia pada remaja putri di SMPN 18 Banjarmasin. Metode observasional analitik dan pendekatan cross sectional. Sampel penelitian remaja putri SMPN 18 Banjarmasin dengan jumlah 50. Pengambilan sampel dengan proportional random sampling. Analisis data menggunakan uji chi square dengan uji alternatif yaitu fisher exact test. Hasil penelitian ini responden yang mengalami anemia 42% dan tidak anemia 58%, siklus menstruasi berisiko 40% dan tidak berisiko 60%, lama menstruasi berisiko 42% dan tidak berisiko 58%, dan volume darah menstruasi berisiko 16% dan tidak berisiko 84%. Hasil analisis uji chi square menunjukkan terdapat hubungan antara siklus dan lama menstruasi dengan kejadian anemia pada remaja putri di SMPN 18 Banjarmasin p=0,000, p=0,000. Hasil analisis fisher exact test menunjukkan tidak terdapat hubungan volume darah menstruasi dengan kejadian anemia pada remaja putri di SMPN 18 Banjarmasin p=0,056. Kata-kata kunci: siklus menstruasi, lama menstruasi, volume darah menstruasi, anemia, remaja putri